miR398 Attenuates Heat-Induced Leaf Cell Death via Its Target CSD1 in Chinese Cabbage - Biting Cao; Jianxia Jiang; Jinjuan Bai; Xuan Wang; Yajie Li; Wenna Shao; Shengwu Hu; Yuke He; Xiang Yu (Horticulturae, 2022)
Previous research has shown that miR398 contributed to plant thermotolerance by silencing its target gene COPPER/ZINC SUPEROXIDE DISMUTASE1 (CSD1) in Arabidopsis thaliana. However, the phylogenesis of miR398 and CSD1 in Brassica crop and their role in regulating leaf cell death under heat stress remains unexplored. Here, we characterized the homologous genes of miR398a and CSD1 in Brassica rapa ssp. pekinensis (Chinese cabbage) and found miR398a abundance was accumulated under heat stress (38 °C and 46 °C for 1 h) in Chinese cabbage, while the expression level of its targets BraCSD1-1 and BraCSD2-1 were downregulated. To further explore their role in heat response, we constructed the transgenic plants overexpressing artificial miR398a (aBra-miR398a), Bra-miR398a target mimic (Bra-MIM398a), and BraCSD1-1 in Chinese cabbage for genetic study. Under high temperatures, p35S::aBra-miR398a lines reduced the areas of leaf cell death and delayed the leaf cell death. By contrast, p35S::Bra-MIM398a and p35S::BraCSD1-1 plants enlarged the areas of leaf cell death and displayed the earliness of leaf cell death. Finally, we found that the expression level of stress-responsive genes BraLEA76, BraCaM1, BraPLC, BraDREB2A, and BraP5CS increased in transgenic plants overexpressing aBra-miR398a, which may contribute to their resistance to heat-induced leaf cell death. Taken together, these results revealed the function of Bra-miR398a in attenuating leaf cell death to ensure plant thermotolerance, indicating that the miR398-CSD1 module could be potential candidates for heat-resistant crop breeding.